General Aspects of Secondary Headaches: a brief Literature Review - Soares, Ana Clara Mendes; Nunes, Melyssa Maria Fernandes da Rocha; Filho, Otavio Pereira da Silva; Lousada, Lívio Martins; Pinheiro, Giulia Rebouças; Azevedo, Marina Pinheiro Uchoa; Coutinho, Isadora Pinheiro; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.